K The Readiness of Implementing Inclusive Education in Early Childhood Education in Teluk Dalam Village: Kesiapan Penyelenggaraan Pendidikan Inklusif pada PAUD di Desa Teluk Dalam - Ratih, Sri; Anisza, Anisza; Farlianti, Juliah Nur; Siregar, Anna Tiana Deli; Handari, Sai; Malik, Lina Revilla (Institut Riset dan Publikasi Indonesia, 2026)
The readiness of Early Childhood Education (PAUD) units in rural areas to implement inclusive education still faces substantial challenges, particularly regarding teachers' pedagogical competence and the accessibility of learning tools. This community service activities aimed to enhance inclusion readiness at two PAUD institutions in Teluk Dalam Village through a concrete intervention program. The implementation method utilized the Asset-Based Community Development (ABCD) approach, comprising three main stages: inclusive classroom management training for teachers, assistance in developing an adaptive curriculum, and workshops on creating adaptive educational play tools utilizing local natural materials (place-based education). The measurement of partner readiness was based on four operational indicators: internal policy, teacher capability, physical facilities, and financial support, with data validation achieved through source triangulation. The results demonstrated a significant impact, notably an increase in teachers' pedagogical readiness in managing heterogeneous classrooms and a reduction in their teaching psychological burden. Furthermore, this program produced a draft for internal school inclusion guidelines and formulated a child-friendly budget policy proposal advocated to the Teluk Dalam Village Government to resolve village fund bureaucratic barriers.